OP0193 Inflammation of adventitial nerves occurs in giant cell arteritis patients and it is characterized by inflammasomes, upr and autophagy activation. (15th June 2017) - Ciccia, F; Rizzo, A; Alessandro, R; Raimondo, S; Guggino, G; Cavazza, A; Salvarani, C; Triolo, G
Abstract : Background: Vascular adventitia is a major site of immune surveillance and inflammatory cell trafficking and is the most complex compartment of the vessel wall comprising fibroblasts, dendritic cells and macrophages, progenitor cells, vasa vasorum, pericytes and adrenergic nerves. It has been proposed that activation of adventitial nerves and release of sensory neuropeptides from their peripheral terminals may leads to neurogenic inflammation. Giant cell arteritis (GCA) is an immune-mediated disease of unknown etiology in which the inflammatory process seems to start from the adventitia of affected arteries. Objectives: aim of the study was to evaluate the occurrence of adventitial nerves inflammation and to immunologically characterize the adventitial neuritis occurring in GCA patients. Methods: Immunohistochemistry and RT-PCR were used to study the presence of neuritis in temporal artery samples obtained from 30 patients with temporal artery (TAB) positive GCA, 20 TAB negative GCA and 20 controls. Laser capture microdissection (LCM) was used to isolate adventitial nerves and nerve expression of pro-inflammatory cytokines involved in the pathogenesis of GCA such as IL-6, IL-17, IL-32, IL-9, IL-33 was assessed by RT-PCR. Expression of pro-inflammatory cytokines by adventitial nerves was further studied by immunohistochemistry and confocal microscopy. Autophagy, unfoled protein response (UPR) and inflammasomes pathways were also studied by RT-PCR and immunohistochemistry. Results: Adventitial nerves showed infiltration of CD3 + T cells in all the TAB positive and in 12 out of 20 TAB negative arteries but were never observed in control arteries. RT-PCR expression analysis of different pro-inflammatory cytokines clearly demonstrated specific over-expression of IL-33 in LCM isolated inflamed nerves. Immunohistochemical and confocal microscopy analysis confirmed nerve IL-33 expression. RT-PCR and immunoistochemistry demonstrated that AIM2 and NLRP3, but not NLCR4, inflammasomes were activated in inflamed nerves of GCA patients. According to inflammasomes activation, increased IL-18 expression was observed. Autophagy-related genes such as ATG16L1 and LC3 and UPR-related genes such as XBP-1 and CHOP were also over-expressed in GCA adventitial nerves as demonstrated by RT-PCR and immunohistochemistry. Finally, increased expression of AIM2 and NLRP3 inflammasomes, autophagy and UPR was also observed outside the nerves, in the context of inflamed artery wall. Conclusions: here we demonstrated that adventitial neuritis is present in both inflamed and non-inflamed arteries of GCA patients. GCA inflamed nerves specifically produce IL-33 a cytokine of the innate immunity that has been demonstrated to be involved in the pathogenesis of GCA. AIM2 and NLRP3 inflammasomes activation was also observed in GCA arteries and in particular in the inflamed adventitial nerves being accompanied by the increased expression of IL-18. Specific activation of autophagy and UPR pathways was also observed in the inflamed GCA nerves. Altogheter these findings seem to suggest a complex immune activation of adventitial nerves in GCA, suggesting a possible role of arterial neuritis in the initiation and perpetuation of GCA artery inflammation. Disclosure of Interest: None declared